Relationship Between Long-Term Objectively Measured Physical Activity and Glycemic Control in Type 2 Diabetes Mellitus Patients: A Prospective Cohort Study - Masuda, Hiroaki; Ishiyama, Daisuke; Yamada, Minoru; Iwashima, Fumiko; Kimura, Yosuke; Otobe, Yuhei; Tani, Naoki; Suzuki, Mizue; Nakajima, Hideki (Diabetes, Metabolic Syndrome and Obesity: Targets and Therapy, 2021)
Increasing physical activity (PA) improves glycemic control in patients with type 2 diabetes mellitus (T2DM). However, whether long-term objectively measured PA is related to glycemic control remains unclear. The aim of this study was to investigate the relationship between long-term objectively measured PA and glycemic control in T2DM patients. This prospective cohort study recruited T2DM patients admitted to a hospital-based diabetes management and education program. The primary outcome was glycemic control by hemoglobin A1c at 6 months after discharge. We defined poor glycemic control according to the Japanese Clinical Practice Guidelines. The PA was objectively measured using a three-axis accelerometer during 6 months' period after discharge. The representative value of PA was the average daily steps during the measurement period and was divided into quartiles. To determine the relationship between the daily steps and poor glycemic control, we performed a multivariate logistic regression analysis. Ninety-four participants were enrolled in the study. Their median age was 59 years, and 38 (40.0%) of them showed poor glycemic control. Multivariate logistic regression analysis showed that the first (Q1, ≤ 6106 steps/day) and second quartiles (Q2, 6107-8258 steps/day) had significantly elevated risks of poor glycemic control compared to Q4 (≥ 10,542 steps/day), with odds ratios of 8.55 [95% confidence intervals (CI) =1.43-51.23] and 15.62 (95% CI 2.63-92.87), respectively. We found that lesser PA was significantly associated with poor glycemic control in T2DM patients. This finding may be beneficial for clinicians while providing long-term advice to diabetic patients.